Kombinasi Akupresur Titik LI4, PC6 (Neiguan), LR3 (Taichong) dan SP6 (San yin jiao) untuk Mengatasi Nyeri Disminorhea pada Remaja di Desa Kesesi - Afifah, Irma; Putri Hardiyanti; Sari, Kartika (Universitas Ngudi Waluyo, 2023)
Dysmenorrhea is a condition that causes pain during menstruation which can cause disruption of activities and requires treatment if the symptoms are severe, and are shown through pain or tenderness in the pelvic area and stomach, dizziness, nausea, vomiting and diarrhea. In the village of Kesesi, there were 50 teenage girls, of which 39 girls experienced menstruation without dysmenorrhea and 11 girls experienced menstruation accompanied by dysmenorrhea. Most young women do not understand how to reduce pain with acupressure techniques. Acupressure is an alternative non-pharmacological treatment for dysmenorrhea. Acupressure is pressing certain body meridian points clockwise for 30 rounds for 3 – 5 minutes. This research aims to provide knowledge to young women who experience dysmenorrhea during their menstrual period with acupressure using a combination of Merdian points LI4, PC6 (Neiguan), LR3 (Taichong) and SP6 (San yin jiao). The method used is the Lecture, Question and Answer and experimental method. Demonstration. The media used are power point slides, and equipment for acupressure practice. This has proven effective in providing clear information and building interaction between facilitators and participants. This combination of methods helps participants understand the material presented well and practice well too. Community service respondents were young women in the village of Kesesi, Pekalongan Regency. The implementation of the activities began with learning about acupressure with counseling on meridian point acupressure to reduce menstrual pain. Evaluation of the participants is carried out by the community service team to obtain analysis and conclusions. Abstrak Dismenore adalah suatu kondisi yang terjadi nyeri saat menstruasi dimana bisa menyebabkan terganggunya kegiatan serta membutuhkan perawatan apabila gejala yang dirasakan berat, serta di tunjukkan melalui rasa sakit ataupun nyeri pada area panggul serta perut, pusing, mual, muntah, dan diare. di desa Kesesi sejumlah 50 remaja putri yang mana diantaranya 39 remaja putri mengalami menstruasi tanpa disertai dismenore dan 11 remaja putri diantaranya mengalami menstruasi dengan disertai dismenore. Remaja putri sebagian besar kurang mengerti bagaimana cara kurangi nyeri dengan teknik akupresure. Akupresure merupakan alternatif penanganan dismenore secara non farmakologi. Akupresure adalah penekanan pada titik meridian tubuh tertentu searah jarum jam sebanyak 30 putaran selama 3 – 5 menit. Penelitian ini bertujuan memberikan pengetahuan pada remaja putri yang mengalami dismenore selama periode menstruasinya dengan akupresure kombinasi titik meredian LI4, PC6 (Neiguan), LR3 (Taichong) dan SP6 (San yin jiao).Adapun metode yang digunakan dengan metode eksperimen Ceramah, Tanya Jawab dan Demonstrasi. Media yang digunakan slide power point, dan perlengkapan untuk praktek akupresure. Hal ini telah terbukti efektif dalam memberikan informasi yang jelas dan membangun interaksi antara fasilitator dan peserta. Kombinasi metode ini membantu peserta memahami dengan baik materi yang disampaikan dan praktik dengan baik pula. Responden pengabdian masyarakat adalah remaja putri di desa kesesi Kabupaten Pekalongan. Pelaksanaan kegitan diawali pewmbelajaran akupresur dengan penyuluhan akupresure titik meredian pengurang nyeri haid. Evaluasi pada para peserta dilakukan oleh tim pengabdian masyarakat sampai mendapatkan analisa dan kesimpulan.